Report of a Working Group on Cucurbits: Second meeting, 8-10 November 2010, Tbilisi, Georgia - Díez, M.J.; Dooijeweert, W. van; Maggioni, L.; Lipman, E.; Bioversity International (2011)
The Second Meeting of the Working Group on Cucurbits was held in Tbilisi, Georgia, on 8 10 November 2010, hosted by the Institute of Farming, Plant Genetic Resources Department.Main achievements of the Working Group included the establishment of the European Central Cucurbits Database (ECCUDB), the development of minimum descriptor lists for melon, cucumber, watermelon and for Cucurbita spp., and progress made in safety-duplication.Steps to follow for the implementation of “A European Genebank Integrated System” (AEGIS) by the Working Group Steps were discussed, stressing the need for improvement of the quality of passport data. Criteria to be used for the selection of Most Appropriate Accessions when dealing with potential duplicates were agreed. A detailed overview of the ECCUDB, which currently included passport data of 27 489 accessions of 21 genera and 72 species, was given. Plans were made for the finalization of the guidelines for the regeneration of cucumber, melon, watermelon and Cucurbita. The status of safety-duplication of cucurbit accessions in European collections was updated. It was also decided to gather information about the non-governmental organizations potentially dealing with on-farm conservation and to record this information in the ECCUDB.